In pursuit of supply chain fit. Issue 3 (12th August 2019) - Sabri, Yasmine
Abstract : Purpose: The purpose of this paper is to develop exploratory propositions and a conceptual framework on the interaction between organisational structure (decision-making centralisation and internal coordination) and the relationship between supply chain fit and firm performance. Design/methodology/approach: Through a case study, two corporate groups with distinctive organisational structures were examined; both are undergoing a critical moment of changes to their top management and are reshaping their corporate and supply chain strategies. Data on decision-making centralisation, internal coordination mechanisms, supply, demand and innovation uncertainties, and supply chain strategies were collected from key respondents. Findings: The analysis conducted suggests the need to consider the joint interaction between organisational structure and supply chain fit in offsetting the implications of a potential misfit on firm performance. Furthermore, the context sensitivity of a supply chain is often overlooked, hence simply modifying supply chain strategy does not necessarily lead to a variation in firm performance. Practical implications: This research is of particular importance to most organisations in the testing times of uncertainty in the global landscape. It guides supply chain practitioners to better understand which elements of the organisational structure interact with the uncertainty of supply, demand and innovation. Originality/value: This paper is one of the first to investigate the interaction between elements of organisational structure and supply chain fit and identify decision-making centralisation and coordination as the internal uncertainty factors that are most relevant to supply chain fit research. A conceptual framework has been built for future testing, in which the organisational structure moderates the relationship between supply chain fit and firm performance.